ECOLOGICAL ASSESSMENT IN SEMARANG COASTAL WATER - Ricky Rositasari; Lestari Lestari (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2013)
Coastal water is vulnerable to anthropogenic substances such as human activities by product in coastal land and  upper land area. Semarang coastal area is one of areas which has progressive development in northern coastal of Java Island.  The aim of this study was to evaluate ocean health status based on heavy metal contain and benthic foraminiferal characteristics as the bioindicator.  Sampling and laboratory activities were carried out in August 2010. Sampling stations were located on the estuaries of Western Canal Flood, Tanjung Mas Port and  Eastern Canal Flood.  The result showed that Tanjung Mas pool port had the highest Pb, Zn,and Total Organic Compounds (TOC) concentrations. The average of abnormal test of benthic foraminiferal (Ammonia beccarii) were also higher in Tanjung Mas port than in eastern and western canal flood. Keywords: assessment, coastal water, Semarang.